Physical and chemical properties of artificial soil with humified and non-humified organic matters - Yeo, Shi Wei (2018)
Considerable research has been carried out on organic soils which consist of various components of organic matter but the effect of particular organic matter is less reported. This may cause some of the contributing factors of each organic matter are not well understood because each type of organic matter have its own characteristic and the effect on the properties of soils is different. Hence, understanding the physico-chemical characteristic of organic soils is the fundamental needs for researcher and important to identify suitable method for further experiment. Artificial soil was used in this study to control the inconsistency of test results which may be obtained due to complexity of characteristics of natural organic soils. The main objective of this study to determine the effect of humified and non-humified organic matter of the soil samples on the physico-chemical and mineralogy, as well as the shear strength. Two types of artificial soils were utilized, namely kaolin mixed with compost (KC) and kaolin mixed with LM Bio Humus Juice (KH). Physical and chemical properties such as Atterberg limit, moisture content, specific gravity and acidity level were determined to establish the basic characteristics of soil. Mineralogy and molecular characteristic of samples were determined based on the XRay Fluorescence (XRF), X-Ray Diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR). Strength of artificial soil was evaluated using unconfined compressive strength test (UCS). Based on the results obtained, compost had changed with decomposition in which it had degraded from fibric peat to hemic peat after a period of 6 months. Decomposition process also affected the physical and chemical properties of artificial soil. Specific gravity of artificial soil KC had reduced with the increment of decomposition period. Humified organic content of compost was found to be increased with decomposition period which shown that the fibres were decomposed. Fiber content had significantly decreased with decomposition period as well as its losses on Ignition (LOI). The strength of soil specimens KC were increased with decomposition period in which the humified matter were increased from 38% to 41% within the test period. The effect of humified matter on strength was tested utilizing artificial soil KH. The plasticity index of artificial soil KH decreased with increment of LM Bio Humus Juice which can be associated with flocculation of soil aggregate. Unconfined compressive strength of artificial soil KH had increased with higher content of LM Bio Humus Juice. The results obtained throughout this study will be beneficial for the understanding on the basic characteristic of organic soil as reference for further experiment in order to identify the strength and improvement method in real construction environment.